Comparable Analysis of Natural and Modified Starches from Kazakhstan: Physicochemical Properties, Applications, and Insights on Biodegradable Films - Marat Muratkhan; Kakimova Zhainagul; Yernaz Yermekov; Kamanova Svetlana; Dana Toimbayeva; Indira Temirova; Kiykbay Amirsana; Dina Khamitova; Yerlan Zharykbasov; Adilet Sugirbay; Saduakhasova Saule; Gulnazym Ospankulova (Applied Sciences)
This study evaluates the potential of natural and thermally modified starches from Kazakhstan, including cassava, potato, wheat, corn, pea, and rice, for the production of biodegradable films. Key physicochemical properties were analyzed using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and a Rapid Visco Analyzer (RVA). The results show that cassava starch, with the highest magnesium content (43.07 mg/100 g) and peak viscosity (1300 RVU), exhibits superior mechanical strength and elasticity, making it ideal for durable agricultural films. Corn starch, with high crystallinity and moderate viscosity (1150 RVU), exhibits excellent stability for long-term applications. In contrast, wheat and rice starches, with lower viscosities (750 and 650 RVU, respectively) and high biodegradability, are more suitable for short-term eco-friendly applications. Modification processes improved moisture resistance and reduced retrogradation tendencies, particularly in cassava and corn starches. SEM analysis revealed that modified starches from cassava and corn have dense and uniform surface structures, enhancing film durability and flexibility. These findings highlight the potential of utilizing Kazakhstan’s starch resources for localized biodegradable film production, reducing reliance on imports while promoting sustainable agriculture.